2018
DOI: 10.1148/radiol.2018171481
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of Solid Pulmonary Nodules at Digital Chest Tomosynthesis: Data from a Cohort of the Pilot Swedish Cardiopulmonary Bioimage Study

Abstract: Purpose To investigate the performance of digital tomosynthesis (DTS) for detection and characterization of incidental solid lung nodules. Materials and Methods This prospective study was based on a population study with 1111 randomly selected participants (age range, 50-64 years) who underwent a medical evaluation that included chest computed tomography (CT). Among these, 125 participants with incidental nodules 5 mm or larger were included in this study, which added DTS in conjunction with the follow-up CT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Simultaneously, the examination can be conducted with a lower radiation dose than that required for chest CT (7)(8)(9). With this advantage, several studies have reported the diagnostic performance of DTS for pulmonary diseases, including lung nodules, mycobacterial infection disease, and lung cancer (10)(11)(12)(13)(14).…”
Section: Digital Tomosynthesis (Dts) Is An Imaging Modality In Which Several Individual Projection Images Are Acquiredmentioning
confidence: 99%
“…Simultaneously, the examination can be conducted with a lower radiation dose than that required for chest CT (7)(8)(9). With this advantage, several studies have reported the diagnostic performance of DTS for pulmonary diseases, including lung nodules, mycobacterial infection disease, and lung cancer (10)(11)(12)(13)(14).…”
Section: Digital Tomosynthesis (Dts) Is An Imaging Modality In Which Several Individual Projection Images Are Acquiredmentioning
confidence: 99%
“…Since the discovery of x-rays in 1895, major advances have taken place in X-ray imaging including computed tomography (CT), dual energy (DE) imaging, cone beam CT (CBCT) and digital tomosynthesis (DT) [1][2][3][4][5][6]. Because these radiologic imaging technologies have been shown to expose the patient to harmful ionizing radiation, rigorous quality assurance (QA) testing is needed to minimize the radiation dose and maximize the diagnostic information from each scan [7].…”
Section: Introductionmentioning
confidence: 99%
“…The Fleischner Society (11) suggests that CXR may be a low-cost/low-dose alternative to CT for the follow-up of larger nodules that are well visualized and considered low risk. In this situation, DTS would be superior as nodule detection is improved compared to CXR (13), although not on par with CT (1417). The question has been raised whether DTS could be an alternative to CT regarding surveillance of indeterminate nodules with low risk of malignancy (14,18).…”
Section: Introductionmentioning
confidence: 99%
“…In this situation, DTS would be superior as nodule detection is improved compared to CXR (13), although not on par with CT (14)(15)(16)(17). The question has been raised whether DTS could be an alternative to CT regarding surveillance of indeterminate nodules with low risk of malignancy (14,18). S€ oderman et al (19) investigated nodule growth on simulated nodules in DTS, and reported that the modality could be applicable, but nodule size, position, and dose level affected the precision of the measurements.…”
Section: Introductionmentioning
confidence: 99%